A systematic review and comparison of questionnaires in the management of spinal cord injury, multiple sclerosis and the neurogenic bladder. Issue 3 (25th January 2015) - Tsang, B.; Stothers, L.; Macnab, A.; Lazare, D.; Nigro, M.
Abstract : Aims: Validated questionnaires are increasingly the preferred method used to obtain historical information. Specialized questionnaires exist validated for patients with neurogenic disease including neurogenic bladder. Those currently available are systematically reviewed and their potential for clinical and research use are described. Methods: A systematic search via Medline and PubMed using the key terms questionnaire(s) crossed with Multiple Sclerosis (MS) and Spinal Cord Injury (SCI) for the years 1946 to January 22, 2014 inclusive. Additional articles were selected from review of references in the publications identified. Only peer reviewed articles published in English were included. Results: 18 questionnaires exist validated for patients with neurogenic bladder; 14 related to MS, 3 for SCI, and 1 for neurogenic bladder in general; with 4 cross‐validated in both MS and SCI. All 18 are validated for both male and female patients; 59% are available only in English. The domains of psychological impact and physical function are represented in 71% and 76% of questionnaires, respectively. None for the female population included elements to measure symptoms of prolapse. Conclusion: The last decade has seen an expansion of validated questionnaires to document bladder symptoms in neurogenic disease. Disease specific instruments are available for incorporation into the clinical setting for MS and SCI patients with neurogenic bladder. The availability of caregiver and interview options enhances suitability in clinical practice as they can be adapted to various extents of disability. Future developments should include expanded language validation to the top 10 global languages reported by the World Health Organization. Neurourol. Urodynam. 35:354–364, 2016 . © 2015 Wiley Periodicals, Inc.